Neurosensory evaluation of inferior alveolar nerve after bilateral sagittal split ramus osteotomy of mandible - P.G. Antony; Aneesh Sebastian; K. George Varghese; C.R. Sobhana; S. Mohan; C.S. Soumithran; Shiney Domnic; N. Jayakumar (Elsevier, 2017)
Mandibular skeletal deformities are mostly corrected by Sagittal Split Ramus Osteotomy. One of the main complications of Bilateral Sagittal Split Ramus Osteotomy is impairement of sensory function of Inferior Alveolar Nerve. Objectives: To evaluate the occurrence of neurosensory disturbance by comparing the subjective and objective assessment of neurosensory responses after bilateral sagittal split ramus osteotomy.To assess the progress of recovery from the first post operative day till six months. To explain the factors causing neurosensory disturbances. Method: A series of 24 patients with clinically and radiographically diagnosed mandibular skeletal deformity were treated with Bilateral Sagittal Split Ramus Osteotomy. For evaluation of the neurosensory responses, the parameters consist of subjective and objective test in order to compare the subjective and objective assessment. Results: On the first post operative day neurosensory disturbances were seen in all the patients. Recovery of sensation was seen in all the patients at the end of this study. Conclusion: The incidence of functional nerve disturbances is acceptable, since the progression towards recovery is inevitable. Prolonged neurosensory disturbance is greatly related to the degree of manipulation of the inferior alveolar nerve.